PTF10iya: A short-lived, luminous flare from the nuclear region of a star-forming galaxy - Cenko, S; Bloom, J; Kulkarni, SR; Strubbe, L; Miller, A; Butler, N; Quimby, R; Gal-Yam, A; Ofek, E; Quataert, E; Bildsten, L; Poznanski, D; et al. (2012)
We present the discovery and characterization of PTF10iya, a short-lived (Δt≈ 10d, with an optical decay rate of ∼0.3magd -1), luminous (mag) transient source found by the Palomar Transient Factory. The ultraviolet/optical spectral energy distribution is reasonably well fitted by a blackbody with T≈ (1-2) × 10 4K and peak bolometric luminosity L BB≈ (1-5) × 10 44ergs -1 (depending on the details of the extinction correction). A comparable amount of energy is radiated in the X-ray band that appears to result from a distinct physical process. The location of PTF10iya is consistent with the nucleus of a star-forming galaxy (z= 0.22405 ± 0.00006) to within 350mas (99.7per cent confidence radius), or a projected distance of less than 1.2kpc. At first glance, these properties appear reminiscent of the characteristic 'big blue bump' seen in the near-ultraviolet spectra of many active galactic nuclei (AGNs). However, emission-line diagnostics of the host galaxy, along with a historical light curve extending back to 2007, show no evidence for AGN-like activity. We therefore consider whether the tidal disruption of a star by an otherwise quiescent supermassive black hole may account for our observations. Though with limited temporal information, PTF10iya appears broadly consistent with the predictions for the early 'super-Eddington' phase of a solar-type star being disrupted by a ∼10 7M ⊙ black hole. Regardless of the precise physical origin of the accreting material, the large luminosity and short duration suggest that otherwise quiescent galaxies can transition extremely rapidly to radiate near the Eddington limit; many such outbursts may have been missed by previous surveys lacking sufficient cadence. © 2012 The Authors Monthly Notices of the Royal Astronomical Society © 2012 RAS.